Sistem Pakar Untuk Mendiagnosa Penyakit Mata Menerapkan Metode Certainty Factor dan Forward Chaining - Marcelino Oktaviansyah; Rima Tamara; Iskandar Fitri (STMIK Budi Darma, 2022)
Disorders of the eye become a disease that is often experienced. There is a new symptom model found, causing confusion that occurs. Diseases of the eye often attack humans, especially in the current era of digital technology, because they spend more time staring at cell phone or computer screens. So the application of this expert system is made to provide solutions for the community to diagnose the symptoms that are often experienced. In making this application, the forward chaining method and certainty factor are used in the application built and comparison with the combined forward chaining and naive Bayes method. The test is carried out by testing 40 data samples based on existing symptoms, carried out by the system and also manually to see the accuracy of the values given. The results given are that there is a fairly high level of certainty in the diagnosis of hypermetropia with a certainty value of 88.43% and the smallest certainty value in the diagnosis of presbyopia with a value of 61.702% of the total testing obtained a probability level of certainty ranging from 51%-79%.